SIMULATING LONG TERM EVOLUTION SELF-OPTIMIZING BASED NETWORKS - Carvalho, Marco António (2013)
With the first 3rd Generation Partnership Project (3GPP) Long Term Evolution (LTE) networks being deployed more complexity is added to current existing cellular mobile networks and more capital (CAPEX) and operational (OPEX) effort will be needed. In addition, the rising demand of users for new services and higher data rates demands more efficiency from operators. For this matter, 3GPP Release 8 as introduced the Self-Organizing Network (SON) concept, a set of self-configuration, self-optimizing and self-healing functions that allow the automation of labor-intensive tasks, reducing operational and capital costs. While requirements on cutting operational expenditure remain, operators still remain skeptical with the efficiency of these functions. In this paper, Physical Cell Identity (PCI) conflict detection and resolution, Automatic Neighbor Relation (ANR) and automatic Handover Parameter Optimization (HPO) functions are proposed as part of a simulator for LTE SON based networks. Based on user defined inputs, these functions allow operators to closely predict and gather optimal policy input values for SON algorithms, while maintaining desirable network performance. Based on a real network scenario, results show simulator’s clear benefit when compared with other proposals.